A probabilistic approach to Wallis' formula. Issue 13 (3rd July 2017) - Wei, Zhengyuan; Li, Juan; Zheng, Xiaoyang
ABSTRACT: We present an alternative proof of Wallis' formula from the probabilistic point of view. Based on the classical central limit theorem, some discrete distributions with additive property, such as binomial, negative binomial, Poisson and multinomial distributions, are considered to derive π/2.